In vivo Assessment of Supra-Cervical Fetal Membrane by MRI 3D CISS: A Preliminary Study - Qi, Wenxu; Zhao, Peinan; Wang, Wei; Sun, Zhexian; Ma, Xiao; Wang, Hui; Wu, Wenjie; Wen, Zichao; Kisrieva-Ware, Zulfia; Woodard, Pamela K.; Wang, Qing; McKinstry, Robert C.; et al. (Frontiers in Physiology, 2020)
In approximately 8% of term births and 33% of pre-term births, the fetal membrane (FM) ruptures before delivery. In vitro studies of FMs after delivery have suggested the series of events leading to rupture, but no in vivo studies have confirmed this model. In this study, we used a three-dimensional constructive interference in steady state (3D-CISS) sequence to examine the FM at the cervical internal os zone during pregnancy; 18 pregnant women with one to three longitudinal MRI scans were included in this study. In 14 women, the FM appeared normal and completely intact. In four women, we noted several FM abnormalities including cervical funneling, chorioamniotic separation, and chorion rupture. Our data support the in vitro model that the FM ruptures according to a sequence starting with the stretch of chorion and amnion, then the separation of amnion from chorion, next the rupture of chorion, and finally the rupture of amnion ruptures. These findings hold great promise to help to develop an in vivo magnetic resonance imaging marker that improves examination of the FMs.